Psychiatric disorders and the onset of self-reported fibromyalgia and chronic fatigue syndrome: The lifelines cohort study - Creed, Francis (Frontiers in Psychiatry, 2023)
Introduction: This study aimed to assess whether psychiatric disorders predict onset of fibromyalgia and chronic fatigue syndrome (CFS) which develop in the presence of pre-existing muscle pain or fatigue. Methods: The population-based Lifelines cohort study included 148,614 adults with relevant data for the fibromyalgia study and 136,423 for the CFS study. Participants with prior self-reported fibromyalgia (or CFS) at baseline were excluded from the relevant analysis. At follow-up (mean 2.4 years) new onsets of each syndrome were identified by self-report. Logistic regression was used to identify which of the baseline variables predicted new onsets of each syndrome. Prior to the analyses the samples were divided into those with and without marked muscle pain (for fibromyalgia analysis) or persistent fatigue (for CFS). Results. During follow-up there were 685/136,423 (0.5%) new onsets of self-reported FM in participants without marked muscle pain and 281/7481 (3.75%) in those with such pain; for CFS it was 292/124,223 (0.2%) for those without and 192/10,025 (1.9%) for those with baseline fatigue. In both univariate and logistic regression analyses of participants with prior persistent fatigue psychiatric disorder was clearly associated with onset of CFS. This was not so for onset of fibromyalgia in participants with prior muscle pain. Discussion. Although psychiatric disorders did not predict self-reported fibromyalgia or CFS in participants free of pain or fatigue at baseline, in this study psychiatric disorder did predict self-reported CFS in the presence of pre-existing fatigue. Progress in understanding the aetiology of these disorders may require studying separately onsets with and without pre-existing key symptoms.